2016
DOI: 10.1074/jbc.m115.701284
|View full text |Cite
|
Sign up to set email alerts
|

The Type IV Pilus Assembly ATPase PilB of Myxococcus xanthus Interacts with the Inner Membrane Platform Protein PilC and the Nucleotide-binding Protein PilM

Abstract: Type IV pili (T4P) are ubiquitous bacterial cell surface structures, involved in processes such as twitching motility, biofilm formation, bacteriophage infection, surface attachment, virulence, and natural transformation. T4P are assembled by machinery that can be divided into the outer membrane pore complex, the alignment complex that connects components in the inner and outer membrane, and the motor complex in the inner membrane and cytoplasm. Here, we characterize the inner membrane platform protein PilC, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 69 publications
(90 reference statements)
3
52
0
1
Order By: Relevance
“…Before manuscript publication, it was demonstrated that PilM directly interacts with PilB in Myxococcus xanthus (67), corroborating our results. Both BfpE, the PilC homologue in the T4bP system, and GspE, the PilB homologue in the T2SS, have been shown to bind to the PilM loop 1B equivalents in BfpC and GspL, respectively (24,51).…”
Section: Discussionsupporting
confidence: 89%
“…Before manuscript publication, it was demonstrated that PilM directly interacts with PilB in Myxococcus xanthus (67), corroborating our results. Both BfpE, the PilC homologue in the T4bP system, and GspE, the PilB homologue in the T2SS, have been shown to bind to the PilM loop 1B equivalents in BfpC and GspL, respectively (24,51).…”
Section: Discussionsupporting
confidence: 89%
“…In this study it was hypothesised that PilB and PilT might function by rotating PilC to stimulate PilA polymerization or depolymerization9. In keeping with this model, PilC was recently shown to interact directly with and stimulate PilB activitiy10.…”
mentioning
confidence: 89%
“…Using this methodology, multiple variations of pET29-based operons were generated, numbering up to seven pil genes. Toxicity/plasmid instability with pET29-based plasmids prompted us to subclone the above operons into the arabinose-inducible pBAD18 (32). Genes or groups of genes were extracted from pET-29 derivatives on an XbaI-XmaI fragment and subcloned into pBAD18 cut with NheI and XmaI.…”
Section: Methodsmentioning
confidence: 99%
“…but there is ample evidence that they establish multiple binary/ ternary interactions at the cytoplasmic membrane (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Moreover, in a recent study in Myxococcus xanthus, in which the entire Tfp machinery was visualized by cryoelectron tomography (34), it was shown that these five proteins form a series of interconnected layers spanning the cytoplasmic membrane, which is a priori compatible with a role in filament assembly.…”
Section: Significancementioning
confidence: 99%